2005
DOI: 10.4037/ajcc2005.14.5.404
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Therapies: A National Survey of Critical Care Nurses

Abstract: • Background Demand for complementary and alternative therapies is increasing and is affecting all healthcare settings, including critical care. • Methods A random sample of members of the American Association of Critical-Care Nurses was surveyed to determine the members’ attitudes, knowledge, perspectives, and use of complementary and alternative therapies. • Results Most of the 726 respondents were using one or more complementary and alternative therapies in practice. The most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 13 publications
6
51
0
3
Order By: Relevance
“…It is interesting to note that the nurses’ interest in learning more knowledge related to CAM has been widely reported in other Western countries and Taiwanese studies (e.g. Strickler 2003, McDowell & Burman 2004, Tracy et al. 2005, Chu & Wallis 2006).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…It is interesting to note that the nurses’ interest in learning more knowledge related to CAM has been widely reported in other Western countries and Taiwanese studies (e.g. Strickler 2003, McDowell & Burman 2004, Tracy et al. 2005, Chu & Wallis 2006).…”
Section: Resultsmentioning
confidence: 78%
“…Without federal regulation, medicines and supplements do not have quality control and, therefore, there is some scepticism about their integrity (Strickler 2003), however, the level of scepticism may vary from country to country. Botting and Cook (2000) and Tracy et al. (2005) reported that the physicians and nurses in their study all required more CAM research evidence before they could judge or recommend it to their clients.…”
Section: Resultsmentioning
confidence: 99%
“…Based on such evidence on may presume that the effect of relaxation and imagery, at least on the anxiety and pain of cardiac patients, is quite powerful, and it warrants further investigation and possibly widespread application in coronary/cardiac units. In fact, in a recent survey (Tracy et al, 2005) more than 55% of intensive care nurses in the United States reported that patients and their families most commonly requested relaxation techniques, as well as prayer, massage or counselling from their nurse. Such mind-body techniques have been practiced by advanced practice nurses (Heath, 1992), and have been applied by specialized centres in intensive care patients for at least a decade (Whitworth et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, physicians in this study who shared the same philosophy as the fathers not only fostered a trusting relationship, but also worked toward the same goals. Thus, nurses in the US (Tracy et al 2005) and UK (Richardson 2001) should familiarise themselves with complementary and alternative therapies to give Chinese fathers of disabled children proper advice and advocacy. Fathers in this study followed religious practices to enhance hope of better outcomes for their disabled children.…”
Section: Combining Therapiesmentioning
confidence: 99%